Usulan Perbaikan Desain Tempat Masak Ergonomis Untuk Warga Lanjut Usia Dengan Pendekatan Focus Group Discussion FGD - Purwanto Purwanto (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2022)
Elderly residents who live in madania homes use the kitchen as a kitchen places for cooking activities, and have complaints about height and slippery floor conditions, according to the elderly as many as 32% of cooking kitchen users representing the elderly population using purposive sampling, proposed design improvements for elderly cooking places by considering the anthropometric size of elderly users, using a focus approach group discussion to facilitate the wishes and complaints experienced by the elderly, the shape and size of the proposed new kitchen design for the elderly by adding a foothold in front of the kitchen to facilitate cooking reach, with a cooking kitchen width: 53 cm; Height: 132cm; length 53 cm, using anthropometric measurements, namely front arm reach (JTD) 53 cm; shoulder width(LB) (maximum) 43 cm; height (TB) 158 cm; elbow height (TS) 132 cm. The design is the result obtained from the first focus group discussion, then the results of the second focus group discussion explain the proposed new design drawings for the elderly's kitchen to the elderly, related to the suggestions obtained from the results of the first focus group discussion and the senior citizens agree with the results drawn, by having a height, width, length according to body size by adding non-permanent footing facilities in front making it easier for users to reach the kitchen for cooking activities, floors that are designed to be safe and non-slippery, and additional cupboard facilities to make it easier to store cooking utensils.Sig (2-tailed) of 0.003 <0.05 indicates that the H1 hypothesis is accepted.